2021
DOI: 10.1093/cid/ciab787
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Four Different Interventions Against Schistosoma haematobium in a Seasonal Transmission Setting of Côte d’Ivoire: A Cluster Randomized Trial

Abstract: Background Annual mass drug administration (MDA) using praziquantel is the cornerstone of schistosomiasis morbidity control, but is not sufficient to interrupt transmission. We implemented a cluster-randomized trial to compare the effectiveness of four different intervention packages to interrupt transmission of Schistosoma haematobium in a seasonal transmission setting of Côte d’Ivoire. Methods Sixty-four localities with a S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…mansoni (n = 10) and both species (n = 8) respectively. Schistosomiasis control strategies were predominantly MDA only in 24 studies and one study each on WASH only [ 19 ]; MDA and WASH [ 20 ]; MDA and snail control [ 21 ]; MDA, behaviour change and snail control [ 22 ]; education and behaviour change [ 23 ]; and MDA and education [ 24 ]. In terms of the diagnostics techniques applied, the majority of studies utilised Kato Kats (n = 10) followed by urine filtration (n = 9); a combination of Kato Katz and urine filtration (n = 6); reagent strips and urine filtration (n = 1) and one study each in Kato Katz and PCR; Kato Katz and ultrasonography; and urine filtration, ELISA and Kato Katz.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…mansoni (n = 10) and both species (n = 8) respectively. Schistosomiasis control strategies were predominantly MDA only in 24 studies and one study each on WASH only [ 19 ]; MDA and WASH [ 20 ]; MDA and snail control [ 21 ]; MDA, behaviour change and snail control [ 22 ]; education and behaviour change [ 23 ]; and MDA and education [ 24 ]. In terms of the diagnostics techniques applied, the majority of studies utilised Kato Kats (n = 10) followed by urine filtration (n = 9); a combination of Kato Katz and urine filtration (n = 6); reagent strips and urine filtration (n = 1) and one study each in Kato Katz and PCR; Kato Katz and ultrasonography; and urine filtration, ELISA and Kato Katz.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that as children get older, their vulnerability to contracting schistosomes increases. In the two study sites, high infection reduction rates (between 96.7 and 99.7%) were attained [ 20 ]. The village that used the canal had a noticeably higher rate of re-infection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prevalence and transmission of schistosomiasis and hookworm in the northern part of Co ˆte d'Ivoire is very low. This calls for attempts to interrupt transmission, as has been tried in a large cluster-randomized trial over a 3-year period prior to this study [48]. Although S. haematobium transmission could not be fully interrupted, preventive chemotherapy, coupled with mollusciding, resulted in marked prevalence reduction.…”
Section: Discussionmentioning
confidence: 99%